Reflections on the shadow carceral state - Murakawa, Naomi (Theoretical criminology, 2024)
In 2012 we urged scholars to explore the extension of penal power through the “shadow carceral state.” The shadow carceral state operates through legally hybrid and institutionally serpentine forms that stretch beyond the criminal legal system. Theoretical Criminology's special issue invited us to reflect on the issues we raised in that piece. We are impressed by the transformation of punishment and society scholarship, which has grown deeper and more sophisticated with each wave of activism. Yet it will take more than a thriving subfield to confront the present and likely future: tenacious and expansive carceral and shadow carceral states that are continually deployed to address the compounding global crises of climate change, mass displacement, and structural poverty.